Religious tolerance in multifaith democracies: a comparative legal study of Indonesia and India - David Pradhan; Haris Haris (Faculty of Law, University of Muhammadiyah Malang, 2021)
This exploratory research Article, based on secondary sources, undertakes a comparative legal study of the Constitutional and statutory provisions as well as recent jurisprudential developments in India and Indonesia for the promotion of religious tolerance in the two diverse, multifaith democracies with a history of social conflict and highly contested religious politics. By adopting the functional method for the comparative legal analysis of the two jurisdictions from Civil Law (Indonesia) and Common Law (India) traditions, the implemental convergence and functional equivalence of the penal laws for preventing communalism and promoting inclusivity and religious amity among the different religious communities in the two States has been elucidated. At the same time, the conceptual and doctrinal differences in jurisprudential understanding of the content, extent, and mechanism for preserving inter-faith amity in the two jurisdictions have been posited to be the result of the divergences in the post-colonial historical trajectories of the two States